2017
DOI: 10.1016/j.yrtph.2017.10.017
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of snus use to diabetes and allied conditions

Abstract: A recent meta-analysis reported smoking to be associated with a 37% higher risk of type 2 diabetes in current smokers, rising to a 57% increase in heavy smokers, which declines on quitting. If the increase results from nicotine exposure, it is possible that using Swedish moist snuff ("snus"), which provides at least equivalent nicotine doses, might also increase diabetes risk. Following a recent publication reporting pooled results from five cohorts, we present a detailed meta-analysis of data from 18 studies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…These current results are consistent with previously published research that showed chewing tobacco increases insulin sensitivity and hyperinsulinemia, which raises the chance of developing diabetes mellitus (14,15,17,18). A few research, however, reported the opposite results (19,20).…”
Section: Discussionsupporting
confidence: 93%
“…These current results are consistent with previously published research that showed chewing tobacco increases insulin sensitivity and hyperinsulinemia, which raises the chance of developing diabetes mellitus (14,15,17,18). A few research, however, reported the opposite results (19,20).…”
Section: Discussionsupporting
confidence: 93%
“…It is similar to another Swedish study that discovered excessive snus intake was independently associated with metabolic syndrome even after adjusting for smoking (Norberg et al, 2006). However, the contrary findings were found in the study conducted by Lee and Thornton (2017); Eliasson et al, (2004); Rasouli et al, (2017) and Rooban et al, (2010) where they reported that use of smokeless tobacco does not increase risk of T2DM.…”
Section: Participantssupporting
confidence: 85%
“…Hypertension and CKD are closely intertwined pathophysiological states; sustained hypertension can lead to the development and progression of end-stage CKD, and conversely, a decline in renal function can lead to the development of hypertension. The association of SLT consumption with type 2 diabetes mellitus has been explored in several studies, and no significant association with a higher risk of diabetes has been reported 32 , although the pathophysiology of this disorder in relation to SLT consumption is yet to be described.…”
Section: Discussionmentioning
confidence: 99%